Transient in situ measurement of kombucha biofilm growth and mechanical properties. Issue 9 (8th April 2021) - Bertsch, Pascal; Etter, Danai; Fischer, Peter
Abstract : Interfacial shear rheology qualifies for transient in situ measurement of kombucha biofilm growth and mechanical properties, revealing that kombucha biofilm formation is a two-step process. Abstract : Kombucha is a traditional beverage obtained by the fermentation of sugared tea by a symbiotic culture of bacteria and yeast which has recently re-emerged as a popular lifestyle product with potential health benefits. The characteristic feature of kombucha is the formation of a cellulosic biofilm due to the excretion of bacterial cellulose with high purity and crystallinity. Despite the growing industrial and technological interest in kombucha, current characterization techniques rely on the periodic sampling of tea broth or biofilm and ex situ analysis of its biochemical or microbial composition. Here, we use interfacial shear rheology (ISR) for the transient in situ determination of kombucha biofilm growth directly at the interface. ISR revealed that kombucha biofilm formation is a two step process with clearly distinguishable growth phases. The first phase can be attributed to the initial adsorption of bacteria at the air–water interface and shows great variability, probably due to varying bacteria content and composition. The second phase is initiated by bacterial cellulose excretion and shows astonishing reproducibility regarding onset and final mechanical properties. Hence, ISR qualifies as a new in situ characterization technique for kombucha biofilm growth and bacterial cellulose production.